Auriculotemporal Neuralgia Secondary to TMJ Synovial Cyst: A Rare Presentation of a Rare Entity. Issue 10 (10th September 2013) - Ansari, Hossein; Robertson, Carrie E.; Lane, John I.; Viozzi, Christopher F.; Garza, Ivan
<x xml:space="preserve">Abstract</x> Synovial cysts of the temporomandibular joint are rare, and to our knowledge, only 14 cases have been reported. The most common presentation is local pain and swelling. We present a case of a synovial cyst presenting with neuralgia in the distribution of the auriculotemporal nerve, initially misdiagnosed as trigeminal neuralgia.